Platelet Count after Single Donor Platelet Transfusion in Patients of Acute Leukemia Receiving Induction Chemotherapy (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine platelet count after single donor platelet transfusion in 24 hours and study confounding effect of induction chemotherapy on platelet count. Patients and Methods: This cross-sectional interventional study was carried out at Oncology Ward, Jinnah Hospital, Lahore. Sixty patients of acute leukemia were included. Admitted, diagnosed cases of acute leukemia with platelet count 20x103/µl were excluded. Results: Out of total 60 cases, 55 patients (91.6%) showed increment in their platelets count while 5 patients (8.3%) showed no increment. After chemotherapy, among acute myeloid leukemia (AML) patients those on anthracycline, 20 out of 27 maintained increments while those on cytosar showed no increment. In acute lymphoid leukemia (ALL) patients, (on L-asparaginase) 30 out of 33 cases did not maintain increment while in 3 cases no net change was seen. Conclusion: Single donor platelets transfusion increased platelets count in AML and ALL patients. This increment is maintained after chemotherapy.
Keywords: Platelet count, Single donor, Platelet Transfusion, Acute leukemia, Induction Chemotherapy